Influence of radioactive isotopes 90Sr, 137Cs, 210Pb on environmental objects and their relationship with bovine leukemia in ecosystems of the Republic of Dagestan - A. R. Mustafayev; E. A. Ivashev (Юг России: экология, развитие)
Aim. To conduct studies on the content of radionuclides 90Sr, 137Cs, 210Pb and determine the total beta‐activity in objects (samples) of the external environment, as well as to investigate the effect of radioactive isotopes on the spread of bovine leukemia in the Republic of Dagestan.Materials and Methods. Samples (haylage, natural grass, silage, compound feed, milk, etc.) that were obtained from various locations of the Republic of Dagestan were used for radiological research. The method of research was radiochemical analysis using the universal spectrometric complex "Gamma Plus", etc. For bovine leukemia the principal material was the reporting data of the Republican Veterinary Laboratory, supplemented by our own research from 1988 to 2008. The research was carried out by generally recognized methods in serology and hematology.Results. After the studies were conducted, a high content of radionuclides 90Sr and 137Cs was found in environmental objects from 1986‐198, and the activity of nuclide 210Pb in the ecosystem of the republic increased tenfold compared to 1985. An important indicator such as the total beta‐activity in the republic also increased in the period (from 1986‐1988) after the accident at the Chernobyl nuclear power station. In 1988, we recorded the maximum number (32.2%) of infected animals with the bovine leukemia virus and in subsequent years the percentage of hemo‐diseased heads of cattle in the farms of the republic increased.Conclusion. Thus, there is a causal relationship between the activity of radionuclides and the decrease in the immune status of animals, which may lead to the increase in the spread of bovine leukemia in the republic.